UNITY IN VARIETY. EMPLOYMENT DYNAMICS AND SPECIALISATION PROFILES OF MEDIUM-SIZED TOWNS IN THE ASTI-ROVIGO AREA, ITALY (2001–2017) - Clerici, Maria Antonietta (Quaestiones Geographicae, 2020)
We still know relatively little about the processes of economic transformation in medium-sized towns, which are the cornerstone of the settlement system of many rural areas, together with small towns. This paper considers a group of 39 towns in Northern Italy, located in the area between Asti and Rovigo. Using data from the Italian National Institute of Data Statistics (ISTAT), we investigated the dynamics of the number of the employed at businesses in the periods of 2001–2011 and 2012–2017, the different specialisations of the towns and their ability to attract employees within the respective employment areas. Locally differentiated performance and evolutionary trajectories are evident, preventing us from being able to think of medium-sized (but also small) towns as a coherent whole. It is also clear how the drive towards centralising employees in towns increased following the Great Recession.